PENINGKATAN KEMAMPUAN GURU UNTUK MENGGUNAKAN MEDIA PEMBELAJARAN DALAM PROSES PEMBELAJARAN MELALUI SUPERVISI AKADEMIK KEPALA SEKOLAH SDN 05/IX JAMBI TULO KABUPATEN MUARO JAMBI - Mursyida (Indonesian Journal of Teacher Education, 2020)
This research was motivated by the low competence of teachers at SDN 05 / IX Jambi Tulo in utilizing media in learning activities. Because of that, this open research was held which aims to help improve the competence of SDN 05 / IX Jambi Tulo teachers in running the media in teaching and learning activities so that students are able to achieve and even meet the minimum completeness criteria of students. As the subject of this school action research, there were 8 teachers from SDN 05 / IX Jambi Tulo, Muaro Jambi Regency. The formulation of the problem of this research is "can the teacher's ability to use learning media at SDN 05 / IX Jambi Tulo be improved through academic supervision by the principal?". The data technique used in this study was to use observation sheets filled in by the supervisor so that the qualitative data was what determined the research that was deployed if the research result indicators were greater than 75. From the observations in cycle 1 the average score of the participants was 73, categorized as yet. successful, because it is still below the performance indicator which is> 75, while in cycle 2 the average overall score of the participants is 85 with good classification. In cycle 2, the research was said to be successful because 85 were above the performance indicators. The success in cycle 2 was due to the media mastery by the participants in cycle I was still not optimal as in cycle 2. There was an increase in understanding of the use of learning media from cycle I to cycle II. The deficiencies in cycle I were improved in cycle II so that it reached a very good level. So it can be said that the academic supervision carried out by the principal in an effort to improve the ability of teachers of SDN 05 / IX Jambi Tulo, Mauro Jambi Regency in using learning media was successful.